2014
DOI: 10.1111/dme.12532
|View full text |Cite
|
Sign up to set email alerts
|

Obesity index and the risk of diabetes among Chinese women with prior gestational diabetes

Abstract: BMI, waist circumference and body fat were all associated with an increased risk of Type 2 diabetes, and waist circumference and body fat were better indicators than BMI for Type 2 diabetes risk among Chinese women with prior gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Further prospective data on women meeting IADPSG criteria only will be useful in clarifying this issue. The factors associated with progression to abnormal glucose tolerance are similar to those noted in previous studies using older criteria -pregnancy OGTT values (fasting glucose in particular) (16,21,22,23,24) and elevated BMI after pregnancy (25,26). Earlier diagnosis of GDM, noted in previous studies as a risk factor (22,24,27,28,29,30), is associated with abnormal glucose tolerance at the first post-partum visit, but not with later progression.…”
Section: Discussionsupporting
confidence: 83%
“…Further prospective data on women meeting IADPSG criteria only will be useful in clarifying this issue. The factors associated with progression to abnormal glucose tolerance are similar to those noted in previous studies using older criteria -pregnancy OGTT values (fasting glucose in particular) (16,21,22,23,24) and elevated BMI after pregnancy (25,26). Earlier diagnosis of GDM, noted in previous studies as a risk factor (22,24,27,28,29,30), is associated with abnormal glucose tolerance at the first post-partum visit, but not with later progression.…”
Section: Discussionsupporting
confidence: 83%
“…Our previous work supported that BMI was associated with an increased risk of type 2 diabetes among women with prior GDM. [33] In the present study, we also found a significant correlation between UA levels and BMI (r 2 = 0.149, P<0.001). Many studies found that the associations between UA levels and the risk of type 2 diabetes or prediabetes somewhat attenuated or vanished when BMI was entered into the models [4,26,28,34].…”
Section: Discussionsupporting
confidence: 80%
“…A total of 4,644 pregnant women who were diagnosed with GDM from 2005 to 2009 and their children in six urban districts were invited to participate in a baseline survey for the TGDMPP. Finally, 1263 GDM women and their children had completed the baseline survey for the TGDMPP from August 2009 to July 2011 (participation rate 27%)193940414243. The study followed the guidelines of the Helsinki Declaration, and was approved by the Human Subjects Committee of the Tianjin Women’s and Children’s Health Center, informed consent was obtained for each participant.…”
Section: Methodsmentioning
confidence: 99%